Influence of Footwear on Posture and Comfort in Elite Rugby Players - Blanchard, Sylvain; Bellaïche, Laurence; Kuliberda, Zbigniew; Behr, Michel (International Journal of Sports Medicine, 2021)
Influence of footwear on posture in athletes is poorly documented despite its potential impact on biomechanics and injury risk. The aim of this study was to investigate effects of different footwear geometries on comfort and posture on a cohort of 48 elite rugby players. Spine posture was characterized by photogrammetry, while center of pressure was measured by means of a force platform. Three different footwear outsoles architectures (one rugby shoe with flat outsole, one rugby shoe with a 10 mm heel rise and foot arch support, and a running shoe with a 10mm heel rise and foot arch support) were compared to non-shod in randomized order. Then comfort felt at the level of foot and spine was also estimated by subjective questionnaires. Compared to the flat rugby model, both other models induced significantly (p<0.05) greater comfort at the level of foot and spine, a slight shift toward of center of pressure and a spinal posture closer to that observed when non-shod. The footwear geometry influences comfort and posture at the level of the foot as well as spine and should be considered in a dual purpose of injury prevention and performance.
Keywords: photogrammetry; biomechanics; rugby boots; spinal posture